A subpopulation of human Adark spermatogonia behaves as the reserve stem cell. Issue 4 (April 2020) - Caldeira-Brant, A L; Martinelli, L M; Marques, M M; Reis, A B; Martello, R; Almeida, F R C L; Chiarini-Garcia, H
Abstract : Human spermatogonial stem cells (SSCs) are an essential source to maintain spermatogenesis as an efficient process for daily sperm production with high self-renewal capacity along adulthood. However, the phenotype and the subpopulation that represent the real reserve SSC for the human testis remain unknown. Moreover, although SSC markers have been described for undifferentiated spermatogonia (Adark and Apale ), the existence of a specific subtype that could be identified as the actual/true SSC has not yet been fully determined. Herein we evaluated spermatogonial morphology, kinetics, positioning regarding blood vasculature in relation to protein expression (UTF1, GFRA1, and KIT) as well as proliferative activity (MCM7) and identified a small subpopulation of Adark with nuclear rarefaction zone (AdVac ) that behaves as the human reserve SSC. We show that AdVac is the smallest human spermatogonial population (10%), staying quiescent (89%) and positioned close to blood vessels throughout most of the stages of the seminiferous epithelium cycle (SEC) and divides only at stages I and II. Within this AdVac population, we found a smaller pool (2% of A undifferentiated spermatogonia) of entirely quiescent cells exhibiting a high expression of UTF1 and lacking GFRA1. This finding suggests them as the real human reserve SSC (AdVac UTF1 + /GFRA1 - /MCM7 - ). Additionally, Adark without nuclear vacuole (AdNoVac ) and Apale have similar kinetic and high proliferative capacity throughout the SEC (47%), indicating that they are actively dividing undifferentiated spermatogonia. Identification of human stem cells with evident reserve SSC functionality may help further studies intending to sort SSCs to treat male diseases and infertility.